World guide to library, archives, and information science associations - Fang, Josephine Riss.; Songe, Alice H.; International Federation of Library Associations and Institutions (Munchen : K.G. Saur, 1990)
This book is targeted at communicating and exchanging information and to co-operate at national and international levels. Knowledge and information contained are regarded vital to the welfare of nations and the world community.
Includes index.
rpm 25/01/2019
Ref.
Keywords: Library; Archives; Information Science